Reduced functional capacity is associated with the proportion of impaired myocardial deformation assessed in heart failure patients by CMR - Hashemi, Djawid; Doeblin, Patrick; Blum, Moritz; Weiss, Karl Jakob; Schneider, Matthias; Beyer, Rebecca; Pieske, Burkert; Duengen, Hans-Dirk; Edelmann, Frank; Kelle, Sebastian (Frontiers in Cardiovascular Medicine, 2023)
Aims Heart failure (HF) does not only reduce the life expectancy in patients, but their life is also often limited by HF symptoms leading to a reduced quality of life (QoL) and a diminished exercise capacity. Novel parameters in cardiac imaging, including both global and regional myocardial strain imaging, promise to contribute to better patient characterization and ultimately to better patient management. However, many of these methods are not part of clinical routine yet, their associations with clinical parameters have been poorly studied. An imaging parameters that also indicate the clinical symptom burden of HF patients would make cardiac imaging more robust toward incomplete clinical information and support the clinical decision process. Methods and results This prospective study conducted at two centers in Germany between 2017 and 2018 enrolled stable outpatient subjects with HF [n = 56, including HF with reduced ejection fraction (HFrEF), HF with mid-range ejection fraction (HFmrEF), and HF with preserved ejection fraction (HFpEF)] and a control cohort (n = 19). Parameters assessed included measures for external myocardial function, for example, cardiac index and myocardial deformation measurements by cardiovascular magnetic resonance imaging, left ventricular global longitudinal strain (GLS), the global circumferential strain (GCS), and the regional distribution of segment deformation within the LV myocardium, as well as basic phenotypical characteristics including the Minnesota Living with Heart Failure Questionnaire (MLHFQ) and the 6-minute walk test (6MWT). If less than 80% of the LV segments are preserved in their deformation capacity the functional capacity by 6MWT (6 minutes walking distance: MyoHealth ≥ 80%: 579.8 ± 177.6 m; MyoHealth 60–<80%: 401.3 ± 121.7 m; MyoHealth 40–<60%: 456.4 ± 68.9 m; MyoHealth < 40%: 397.6 ± 125.9 m, overall p-value: 0.03) as well as the symptom burden are significantly impaired (NYHA class: MyoHealth ≥ 80%: 0.6 ± 1.1 m; MyoHealth 60–<80%: 1.7 ± 1.2 m; MyoHealth 40–<60%: 1.8 ± 0.7 m; MyoHealth < 40%: 2.4 ± 0.5 m; overall p-value < 0.01). Differences were also observed in the perceived exertion assessed by on the Borg scale (MyoHealth ≥ 80%: 8.2 ± 2.3 m; MyoHealth 60–<80%: 10.4 ± 3.2 m; MyoHealth 40–<60%: 9.8 ± 2.1 m; MyoHealth < 40%: 11.0 ± 2.9 m; overall p-value: 0.20) as well as quality of life measures (MLHFQ; MyoHealth ≥ 80%: 7.5 ± 12.4 m; MyoHealth 60–<80%: 23.4 ± 23.4 m; MyoHealth 40–<60%: 20.5 ± 21.2 m; MyoHealth < 40%: 27.4 ± 24.4 m; overall p-value: 0.15)–while these differences were not significant. Conclusion The share of LV segments with preserved myocardial contraction promises to discriminate between symptomatic and asymptomatic subjects based on the imaging findings, even when the LV ejection fraction is preserved. This finding is promising to make imaging studies more robust toward incomplete clinical information.